2020
DOI: 10.7759/cureus.12298
|View full text |Cite
|
Sign up to set email alerts
|

Energy Drinks: A Reversible Risk Factor for Atrophic Gastritis and Gastric Intestinal Metaplasia

Abstract: Energy drinks (ED) are becoming increasingly popular, but little has been reported about their stomach effects. To our knowledge, there is no literature suggesting an association with the development of atrophic gastritis (AG) or gastric intestinal metaplasia (GIM). AG and GIM have been associated with an increased risk of gastric cancer. Reversal of these lesions has shown to reduce the incidence of gastric cancer but has only been studied to eradicate Helicobacter pylori. This case describes a female who con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Goblet cell metaplasia encountered in this group may be a marker for an early progression to gastric cancer [16]. This finding goes with finding of Garg et al who described the presence of atrophic gastritis and gastrointestinal metaplasia in relation to increase the dose of energy drinks [17]. Regarding intestinal sections, normal histological pattern was found in control group.…”
Section: Discussionsupporting
confidence: 87%
“…Goblet cell metaplasia encountered in this group may be a marker for an early progression to gastric cancer [16]. This finding goes with finding of Garg et al who described the presence of atrophic gastritis and gastrointestinal metaplasia in relation to increase the dose of energy drinks [17]. Regarding intestinal sections, normal histological pattern was found in control group.…”
Section: Discussionsupporting
confidence: 87%
“…The last finding also demonstrated that EDs containing caffeine can stimulate gastrin and gastric acid secretion and may reduce the competence of the lower esophageal sphincter, which eventually leads to gastroesophageal reflux disease (GERD) [ 64 , 73 ]. Interestingly, a case study revealed that atrophic gastritis and the gastric intestinal metaplasia can be limited with the withdrawal of EDs [ 74 ].…”
Section: Alarming Effects Associated With Energy Drink Consumptionmentioning
confidence: 99%
“…Headaches and stomach aches are known as common side effects of the excessive intake of caffeine ( 59 , 60 ). Hence, the coexistence of more reported headaches and stomach aches among those with more frequent consumption of CED is expected, and comes in line with the existing literature linking CED with such adverse symptoms ( 61 , 62 ).…”
Section: Discussionmentioning
confidence: 99%